Globalization backlands: labor and territory - Jacob Carlos Lima; Roseli de Fátima Corteletti; Iara Maria de Araújo (Frontiers in Sociology)
This text analyses the relationship between work and territory, focusing on the diverse processes involved in integrating places into the logic of capitalist production, and the role of the state in this integration. Taking the neoliberal policies of the Brazilian state since the 1990s and the inclusion of peripheral territories in the clothing sector’s outsourcing processes as its starting point, it explores the reinterpretation of informal production hubs in a model of individual self-entrepreneurship with cost reduction and increased national competitiveness, on the one hand, and the implementation of policies to reduce labor costs and attract companies to organize outsourcing networks based on the supply of cheap labor and its symbolic value, represented by the offer of formal jobs in a region where these are scarce commodities, on the other hand. Based on two distinct empirical cases, the text demonstrates how informal production hubs are being reinterpreted within a model of individual self-entrepreneurship, which involves reducing costs and increasing national competitiveness. It also shows how policies are being implemented to reduce labor costs and attract companies to organize outsourcing networks based on the supply of cheap labor, as well as the symbolic value of offering formal jobs in a region where these are scarce. The text assumes that the state shapes work territories through regulation, promotion or exclusion, resorting to different policies to this end. In territories traditionally characterized by precariousness, this intervention is perceived as a positive development compared to a previous situation in which employment and income opportunities were limited. This reflects the social, political and cultural relations that shape the space, integrating it into the logic of accumulation. The research was conducted between 2017 and 2019, with the data being updated in 2024. It consisted of exploratory visits to cities and production workshops, as well as interviews with owners and workers of these places.